Variability in the organization and size of hunter-gatherer groups: Foragers do not live in small-scale societies. Issue 131 (June 2019) - Bird, Douglas W.; Bird, Rebecca Bliege; Codding, Brian F.; Zeanah, David W.
Abstract: Mobile hunter-gatherers are often characterized as living in small communities where mobility and group size are products of the environmentally determined distribution of resources, and where social organization is multi-scalar: groups of co-residents are nested within small communities that are, in turn, nested within small-scale societies. Such organization is often assumed to be reflective of the human past, emerging as human cognition and communication evolved through earlier fission-fusion social processes, typical of many primate social systems. We review the history of this assumption in light of recent empirical data of co-residence and social networks among contemporary hunter-gatherers. We suggest that while residential and foraging groups are often small, there is little evidence that these groups are drawn from small communities nested within small-scale societies. Most mobile hunter-gatherers live in groups dominated by links between non-relatives, where residential group membership is fluid and supports large-scale social networks of interaction. We investigate these dynamics with fine-grained observational data on Martu foraging groups and social organization in Australia's Western Desert. The composition of Martu foraging groups is distinct from that of residential groups, although both are dominated by ties between individuals who have no close biological relationships. The number of individuals in a foraging group varies with habitat quality, but in a dynamic way, as group size is shaped by ecological legacies of land use. The flexible size and composition of foraging groups link individuals across their "estates": spatially explicit storehouses of ritual and relational wealth, inherited across generations through maintaining expansive networks of social interaction in a large and complex society. We propose that human cognition is tied to development of such expansive social relationships and co-evolved with dynamic socio-ecological interactions expressed in large-scale networks of relational wealth.